A Cross-Linguistic Comparison of Hedging Density Across Sections in Academic Research Articles - Yenni Arif Rahman; Fitri Yeni; Fitri Apriyanti; Fiza Asri Fauziah Habibah (Universitas Islam Negeri Palopo, 2025)
In academic writing, hedging is a key rhetorical strategy that allows researchers to express caution and manage claims with appropriate nuance. This study investigates hedging practices in Applied Linguistics research articles written by Indonesian and Native English authors. Using a corpus of 20 articles (10 per group) totaling approximately 100,000 words, the analysis focuses on hedging density, distribution across Introduction, Methods, Results, and Discussion sections, and types of hedging devices used. Native English authors employ significantly more hedging devices (859 total) than Indonesian authors (365 total), especially modal and epistemic verbs. Both groups hedge most in the Introduction and Discussion sections, with statistically significant higher hedging densities among Native English writers in these parts, while the Methods section exhibits the least hedging for both. Indonesian authors favor approximators as hedging devices, indicating cultural preference for indirect lexical softening, contrasted with the more explicit grammatical hedging by Native English authors. These results highlight distinct cultural rhetorical preferences and suggest that academic writing pedagogy for Indonesian scholars should incorporate modal and epistemic verb strategies to better align with international norms.